2004
DOI: 10.1128/jb.186.10.3124-3132.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monospecies Biofilm Formation by Helicobacter pylori

Abstract: As all bacteria studied to date, the gastric pathogen Helicobacter pylori has an alternate lifestyle as a biofilm. H. pylori forms biofilms on glass surfaces at the air-liquid interface in stationary or shaking batch cultures. By light microscopy, we have observed attachment of individual, spiral H. pylori to glass surfaces, followed by division to form microcolonies, merging of individual microcolonies, and growth in the third dimension. Scanning electron micrographs showed H. pylori arranged in a matrix on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
186
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(213 citation statements)
references
References 49 publications
(43 reference statements)
10
186
0
7
Order By: Relevance
“…In E. coli O157:H7, indole has the opposite effect of reducing attachment to both abiotic surfaces and epithelial cells (8). While mucin is thought to enhance P. aeruginosa attachment and biofilm formation in the lungs (88), it serves to promote planktonic growth of Helicobacter pylori within the stomach environment (25). Observations such as these underscore the importance of extracellular cues in driving attachment but also caution against making generalizing conclusions regarding the universal impact of particular environmental conditions on adherence capabilities of various bacterial species.…”
Section: Why Attach In the First Place?mentioning
confidence: 99%
“…In E. coli O157:H7, indole has the opposite effect of reducing attachment to both abiotic surfaces and epithelial cells (8). While mucin is thought to enhance P. aeruginosa attachment and biofilm formation in the lungs (88), it serves to promote planktonic growth of Helicobacter pylori within the stomach environment (25). Observations such as these underscore the importance of extracellular cues in driving attachment but also caution against making generalizing conclusions regarding the universal impact of particular environmental conditions on adherence capabilities of various bacterial species.…”
Section: Why Attach In the First Place?mentioning
confidence: 99%
“…It seems that H. pylori favours planktonic growth over biofilm formation in the mucous-rich stomach. The luxS mutant strains of H. pylori SD14 and SD3 showed two-to threefold increased biofilm formation as compared to their wild type strains [50]. These data show that a luxS mutant alters biofilm formation in both C. jejuni and H. pylori strains but with opposite outcome.…”
Section: Biofilm Formationmentioning
confidence: 48%
“…These authors have thus suggested the ability of H. pylori to produce self-inhibiting substances with bacteriostatic activity. It appears, however, that the effect of the apparent inhibition of the bacteria was due to the transition of the microorganisms into the VBNC state, which in the case of H. pylori is connected with spiral-to-coccoid transformation (9,10,14,22,33). Cis-2-tetradecenic acid (C 14 :Δ 2 ), which is produced by X. fastidiosa, is responsible for biofilm formation and autoaggregative behavior associated with the increased synthesis of hemagglutinin-like HxfA/B proteins.…”
Section: Communication Of Microorganisms Via Diffusible Signal Factorsmentioning
confidence: 99%
“…The altered phenotype and transcription of these genes was restored by the exogenous addition of AI-2 or 4,5-dihydroxy-2,3-pentandione (DPD, an AI-2 precursor) to the culture medium or by complementing the luxS gene. The experiment conducted by Cole et al (33) showed that H. pylori luxS mutants have the ability to grow in a similar manner as wild-type strains, i.e. there were no defects in adhesion, formation of microcolonies or spatial biofilm structure, or in physiological transition of bacteria from the spiral to the coccoid form.…”
Section: H Pylori Morphological Formsmentioning
confidence: 99%